Newly Developed Nonlinear Vehicle Model for an Active Anti-roll Bar System - Noraishikin Binti Zulkarnain; Hairi Zamzuri; Sarah ’Atifah Saruchi; Mohd Marzuki Mustafa; Siti Salasiah Mokri; Nurbaiti Wahid; Siti Nor Zawani Ahmmad; Alias Jedi (Institute of Advanced Engineering and Science, 2018)
This paper presents the development of a newly developed nonlinear vehicle model is used in the validation process of the vehicle model. The parameters chosen in a newly developed vehicle model is developed based on CARSIM vehicle model by using non-dominated sorting genetic algorithm version II (NSGA-II) optimization method. The ride comfort and handling performances have been one of the main objective to fulfil the expectation of customers in the vehicle development. Full nonlinear vehicle model which consists of ride, handling and Magic tyre subsystems has been derived and developed in MATLAB/Simulink. Then, optimum values of the full nonlinear vehicle parameters are investigated by using NSGA-II. The two objective functions are established based on RMS error between simulation and benchmark system. A stiffer suspension provides good stability and handling during manoeuvres while softer suspension gives better ride quality. The final results indicated that the newly developed nonlinear vehicle model is behaving accurately with input ride and manoeuvre. The outputs trend are successfully replicated.